The Effects of Second Language Learning on First Language Production: A Code-Switching Study of an Indonesian-English Bilingual - Nurdiana Nurdiana (Universitas Bunda Mulia, 2020)
As bilingual behavior, code-switching has always been an interesting topic to discuss. Milroy and Muysken (in Chloros, 2009:9) state that code-switching is probably the fundamental issue in research related to bilingualism. This paper discusses a code-switching study of an Indonesian-English bilingual who does code-switching very often when talking to an Indonesian who speaks English fluently and accurately. The data were taken from several sources: a chat in yahoo messenger, a chat in short messaging service (SMS), a conversation recorded in a mobile phone, a short paragraph written by the informant, and regular observation. The results of the research show the types of code-switching that appeared during the research are inter- and intra-sentential.